2013
DOI: 10.1002/ppul.22825
|View full text |Cite
|
Sign up to set email alerts
|

SFTPC gene mutation p.R167Q in a premature infant

Abstract: We present an infant who was born premature at 23 weeks gestation with bronchopulmonary dysplasia and a SFTPC gene mutation, p.R167Q, who had a complicated neonatal course requiring 4 months of mechanical ventilation. Over time, his clinical course has improved, and he only requires oxygen by nasal cannula and low dose hydroxychloroquine, suggesting that p.R167Q mutation contributed to his clinical course and may manifest with a variable disease pattern making long-term prognostication difficult in the immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We then reviewed a total of 48 full‐text articles out of which 14 were deemed ineligible for inclusion (i.e., articles were editorials or review articles, no mutations were reported, cases were included in other publications, or there were insufficient phenotypic detail). Three articles were excluded due to uncertainty as to whether the reported mutations were likely to be disease‐causing. One article was excluded because it had been retracted by the authors .…”
Section: Methodsmentioning
confidence: 99%
“…We then reviewed a total of 48 full‐text articles out of which 14 were deemed ineligible for inclusion (i.e., articles were editorials or review articles, no mutations were reported, cases were included in other publications, or there were insufficient phenotypic detail). Three articles were excluded due to uncertainty as to whether the reported mutations were likely to be disease‐causing. One article was excluded because it had been retracted by the authors .…”
Section: Methodsmentioning
confidence: 99%
“…There are case reports about HCQ treatment and its benefit in infants with bronchopulmonary dysplasia and surfactant protein C p.Cys121Gly mutation at a dose of 10 mg/kg per day. 9 10 HCQ was used for 6 months and no adverse reaction was recorded. The author concluded that anti-inflammatory properties of the drug should have an impact on the clinical course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been determined that HCQ reduces the level of cytokines such as IL-1, TNF-α secreted by macrophages, and impedes autophagy 6,7 . HCQ is safe and compatible with pregnancy and breastfeeding, besides a few reports about HCQ treatment in infants with interstitial lung disease were published [8][9][10] . The action of mechanism is thougt to be due to its anti-inflammatory properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations